Causes of the Crisis in the Electricity Industry and Future Policy Directions - Ilchong Nam (Korea Development Institute (KDI), 2013)
- In 2001, South Korea restructured its electric power industry and introduced competition to the industry, but it has failed to establish an effective system of competition. - Since the restructuring took place in 2001, electric power is being produced and investment is being made in power generation facilities through competition between generation companies. However, due to structural problems in the market transaction system that determine the actual effectiveness of competition in the electric power industry, this competition is not taking place effectively. - Furthermore, the price regulation system for the transmission, distribution, and retailing of electricity, which remain under monopoly control, and the ownership structure of Korea Electric Power Corporation (KEPCO) and KEPCO's subsidiary generation companies remain stuck in the mindset of the government monopoly system that preceded the restructuring. As a result, KEPCO and its subsidiaries continue to experience internal inefficiency, and the distribution of resources within the power industry continues to be inefficient as well. - The chronic supply crisis, the unending inadequacy of facilities, the excessive consumption of power, KEPCO's large-scale accumulated deficit, the inefficient management of KEPCO and its subsidiary generation companies, and the frequent accidents that have occurred over the past few years are all caused by the failure of policies concerning management, regulation, and government-run companies in the power industry. - In order to normalize the power industry and increase its efficiency, it is necessary to strengthen policies governing competition in the power industry. It is also necessary to implement the kind of pricing and government-run company governance systems that are used in advanced countries, systems that are grounded in the profit motive and economic efficiency. - In the wholesale power market, direct price competition should be permitted under a price cap, just as in the PJM market in the eastern US. In the capacity market, the current spot market format should be converted to a forward contract market that takes into account the time required for investment in facilities. - The system must be changed to eliminate excessive profit, which violates market principles, without hampering competition. Vesting contracts should be introduced to baseload plants and other power generation facilities that were constructed in the past; entrance limitations should be abolished for the construction of additional baseload plants; and business operators should be chosen through competitive bidding in cases where there is some kind of entrance barrier resulting from location or environmental issues. - After introducing optimal rate-of-return regulations in the respective categories of transmission, distribution, and retailing, these regulations should be converted to price cap regulations early on. In addition, the governance structure of KEPCO and its subsidiary utilities must be reoriented toward maximizing the profit motive and giving management more discretion so that these government-run companies can compete with companies in the private sector. - The power industry as it exists today has dealt with instability for the 10 years that have passed since 2003. The structure of the industry must also be reoriented to maximize competition.
Keywords: 330